Comprehensive Management of Child Maltreatment Syndrome: A Case Study and Clinical Implications in An Infant - Kowalczyk, Emilia; Koziej, Sylwia; Borkowska, Joanna; Bajorek, Julia (Quality in Sport, 2024)
Introduction and purpose The World Health Organization (WHO) defines violence against children as “all forms of physical and emotional maltreatment, sexual abuse, neglect and exploitation that result in actual or potential harm to a child’s health, development or dignity.” In Poland, 17,392 cases of violence against children and adolescents were reported in 2015. In the U.S. in 2012, 3.4 million children were reported to facilities for maltreatment. Violence against children leads to serious health problems, both physical and mental, as well as long-term social consequences. Despite its prevalence, many cases remain unreported, with victims, particularly infants, being highly vulnerable. In the case described, a boy born at 36 weeks gestation was admitted to the hospital with symptoms of apathy. Examination revealed neurological symptoms, multiple intracranial hematomas, skull bone fractures and hearing loss. The ophthalmic consultation and examination revealed the presence of retinal hemorrhages, confirming the diagnosis of child maltreatment syndrome. Prompt medical and legal intervention allowed the child’s condition to be stabilized, allowing for proper further development in foster care. This article presents a clinical case of maltreatment syndrome in an infant, with a discussion of complications and abnormalities in the performed investigations and a discussion of the treatment administered. Conclusion Prompt recognition of such cases is vital, considering the potential long-term physical and psychological consequences. Practical implications for medical personnel and the need to cooperate with social and legal institutions to provide adequate care for abused children are discussed. The presented case underscores the need for comprehensive approaches to address child maltreatment, involving medical, legal, and social interventions to safeguard the welfare of affected children.